Investigation of Trade Credit Demand Patterns in Effect with Firm-Bank Relationship: A Panel Data Approach - Ahmed, Jaleel; Xiaofeng, Hui; Khan, Shahid Kalim (Journal of Asian Business Strategy, 2015)
This research paper investigates the behavior of non-financial firms towards trade credit demand in a developing economy while focusing on firm-bank relationship. We have analyzed data from 2005 to 2011 for 220 listed non-financial firms, including manufacturing and services industries. This study reveals that joint board of directors of a firm and a commercial bank leads to easy availability of bank loan and thus decrease firm’s demand for trade credit. Moreover, some control variables like fixed assets, inventory and size has been found significant for trade credit demand.